Further records of the anchialine shrimp, Periclimenes pholeter Holthuis, 1973 (Crustacea, Decapoda, Palaemonidae) - de Grave, S.; Sakihara, T. S. (Zootaxa, 2011)
Caridean shrimps are one of the most conspicuous faunal components of the Indo-West Pacific anchialine fauna (Maciolek, 1983). To date, 11 anchialine species distributed in 10 genera and 5 families have been recorded in Indo-Pacific waters, with related species occurring in Atlantic waters, notably in Mexican cenotes and caves in the Bahamas.